Proteogenomic characterization of primary colorectal cancer and metastatic progression identifies proteome-based subtypes and signatures - Atsushi Tanaka; Makiko Ogawa; Yihua Zhou; Kei Namba; Ronald C. Hendrickson; Matthew M. Miele; Zhuoning Li; David S. Klimstra; Patrick G. Buckley; Jeffrey Gulcher; Julia Y. Wang; Michael H.A. Roehrl (Cell Reports, 2024)
Summary: Metastatic progression of colorectal adenocarcinoma (CRC) remains poorly understood and poses significant challenges for treatment. To overcome these challenges, we performed multiomics analyses of primary CRC and liver metastases. Genomic alterations, such as structural variants or copy number alterations, were enriched in oncogenes and tumor suppressor genes and increased in metastases. Unsupervised mass spectrometry-based proteomics of 135 primary and 123 metastatic CRCs uncovered distinct proteomic subtypes, three each for primary and metastatic CRCs, respectively. Integrated analyses revealed that hypoxia, stemness, and immune signatures characterize these 6 subtypes. Hypoxic CRC harbors high epithelial-to-mesenchymal transition features and metabolic adaptation. CRC with a stemness signature shows high oncogenic pathway activation and alternative telomere lengthening (ALT) phenotype, especially in metastatic lesions. Tumor microenvironment analysis shows immune evasion via modulation of major histocompatibility complex (MHC) class I/II and antigen processing pathways. This study characterizes both primary and metastatic CRCs and provides a large proteogenomics dataset of metastatic progression.